Preparation method of chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide
By using a chitosan-based bilayer structure loaded with curcumin and calcium peroxide in diabetic wound dressings, using microfluidic nano-aerosol spray spinning technology and multi-dimensional backpack optimization algorithm, the problem of difficult coordination between the water absorption performance and the unidirectional derivation ability of the unidirectional derivation ability of the unidirectional derivation of the diabetic wound dressings is solved, and the effective unidirectional derivation of the nucleus and the stability of the wound healing environment is achieved.
Patent Information
- Application Number
- CN202510078540.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-22
AI Technical Summary
Existing diabetic wound dressings are difficult to coordinate between water absorption performance and the unidirectional deduction ability of exudate, resulting in increased risk of lateral leakage of exudate, wound discomfort and infection.
The chitosan-based bilayer diabetic wound composite dressing loaded with curcumin and calcium peroxide was used to prepare nanofibers by microfluidic nanogas spray spinning technology, and the processing process parameters were determined through a multi-dimensional backpack optimization algorithm, combining the padding and freeze-drying processes to form an asymmetric structure of the hydrophobic bottom layer and the hydrophilic top layer.
The one-way lead-out of the exudate is achieved, the reverse penetration of the exudate is avoided, the liquid absorbency rate and one-way guide wet ratio of the dressing are significantly improved, and the stability of the wound healing environment is enhanced.
Smart Images

Figure CN119857163A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical composite dressings, and in particular relates to a method for preparing a chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide. Background Art
[0002] Diabetic wound healing is a complex physiological process, and effective management of wound exudate is crucial to healing. Traditional diabetic wound dressings mainly include alginate dressings, hydrocolloid dressings, foam dressings, etc. These dressings maintain a suitable moist environment for the wound by absorbing wound exudate. Among them, alginate dressings have good water absorption properties and can absorb a large amount of wound exudate; hydrocolloid dressings can form gels to keep the wound moist; foam dressings have a certain buffering effect and can reduce wound pressure. These dressings have been widely used in clinical practice and have played an important role in promoting wound healing.
[0003] However, traditional dressings have obvious limitations. First, most dressings only have a single function, either focusing on water absorption performance or focusing on exudate management, and it is difficult to achieve the synergy of multiple functions. Secondly, traditional dressings are prone to lateral leakage after absorbing exudate, causing maceration of the surrounding skin and affecting wound healing. In addition, the adhesion problem between the dressing and the wound is also prominent, and it is easy to cause secondary damage to the wound when changing the dressing. Most importantly, existing dressings generally lack the ability to directional guide the exudate and cannot effectively achieve one-way drainage of the exudate, which causes the exudate to accumulate around the wound and increases the risk of infection.
[0004] That is to say, there is a technical problem in the prior art that the water absorption performance of diabetic wound dressings and the unidirectional drainage capability of exudate are difficult to coordinate.
[0005] Therefore, how to ensure that the dressing has good water absorption performance while achieving unidirectional drainage of exudate has become a key technical problem that needs to be solved urgently. Although some studies have tried to improve the performance of dressings by constructing gradient structures or introducing hydrophobic modifications, these methods often affect the basic water absorption performance of the material, or the preparation process is too complicated to achieve large-scale production. Summary of the invention
[0006] In view of this, the present invention provides a method for preparing a chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide, which can solve the technical problem in the prior art that the water absorption performance of the diabetic wound dressing and the unidirectional drainage ability of the exudate are difficult to coordinate.
[0007] The present invention is implemented as follows: the present invention provides a preparation method of a chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide, comprising the following steps: preparing a mixed spinning solution of chitosan and polyethylene oxide, preparing nanofibers by microfluidic nano air jet spinning technology, determining processing parameters by a multidimensional backpack optimization algorithm, loading curcumin by a padding process after immersion treatment; preparing a sodium alginate solution and a chitosan solution, adding calcium peroxide to prepare a mixed solution, and preparing aerogel by a freeze-drying process; placing the curcumin-modified nanofibers on a bottom layer, and placing the calcium peroxide aerogel on a top layer for hot pressing and compounding to obtain the double-layer diabetic wound composite dressing.
[0008] Among them, the step of preparing the mixed spinning solution is specifically to mix chitosan with a deacetylation degree of 80 to 95% and a weight average molecular weight of 180 kilodaltons and polyethylene oxide with a viscosity average molecular weight of 600 kilodaltons in a mass ratio of 40:60 to 60:40, add 50% by mass acetic acid and 40% by mass deionized water, and stir at room temperature for 12 to 24 hours.
[0009] Among them, the step of using a multidimensional backpack optimization algorithm to determine the processing parameters is specifically to set the solution advancement rate to 0.5 to 3.0 ml per hour, the air pressure value to 0.06 to 0.14 MPa, the ambient humidity value to 20 to 40%, the nozzle distance of the spinning machine to 25 to 36 cm, the receiver speed of the spinning machine to 800 to 1400 revolutions per minute, and the spinning time to 6 hours.
[0010] Among them, the nanofiber soaking treatment step is specifically to place the nanofiber in a vacuum environment of 25 degrees Celsius for 24 to 48 hours, soak the treated nanofiber in anhydrous ethanol for 12 to 48 hours, soak the soaked nanofiber in deionized water for 20 to 60 minutes, and freeze-dry the soaked nanofiber for 24 to 48 hours.
[0011] Among them, the step of loading curcumin by the padding process is specifically to prepare a curcumin anhydrous ethanol solution with a concentration of 25 to 100 micromoles per liter, the pressure value of the padding process is 0.5 to 2.0 MPa, the roller speed of the padding process is 0.5 to 1.5 revolutions per minute, the number of padding times of the padding process is 5 to 15 times, and the modified nanofibers are dried in an environment of 30±5 degrees Celsius for 10 to 30 minutes.
[0012] The step of preparing the sodium alginate solution specifically comprises dissolving the sodium alginate in deionized water and stirring for 8 to 12 hours to obtain a sodium alginate solution with a mass fraction of 5 to 10%.
[0013] The step of preparing the chitosan solution is to dissolve chitosan with a deacetylation degree of 87.5±7.5% and a weight average molecular weight of 180 kilodaltons in a mixture of acetic acid and deionized water at a pH of 5 and stir for 8 to 12 hours to obtain a chitosan solution with a mass fraction of 5 to 10%.
[0014] The step of preparing the mixed solution is to mix the sodium alginate solution with the chitosan solution, add glycerol accounting for 10% of the total mass of the mixed solution, add calcium peroxide with a mass fraction of 1 to 3%, and stir for 20 to 60 minutes to obtain the mixed solution.
[0015] Among them, the step of preparing aerogel is specifically to introduce the mixed solution into a 24-well plate, freeze it at a temperature of minus 20±5 degrees Celsius for 24 to 48 hours, and place the frozen mixed solution in a freeze dryer at a temperature of minus 40±10 degrees Celsius for 36 to 48 hours.
[0016] Among them, the step of hot pressing and compounding is specifically to hot press for 10 to 15 minutes at a temperature of 40 to 60 degrees Celsius and a pressure of 10 to 15 MPa to obtain the double-layer diabetic wound composite dressing.
[0017] Compared with the prior art, the present invention provides a method for preparing a chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide. The double-layer composite dressing proposed by the present invention achieves the synergy of water absorption performance and unidirectional exudate extraction function through ingenious structural design and material selection. The bottom layer adopts CS / PEO nanofiber modified with curcumin, which is hydrophobic and can prevent the exudate from flowing back; the top layer adopts CS / SA / CaO2 aerogel, which has super water absorption and can quickly absorb and lock the exudate. This asymmetric structural design ensures that the exudate can only migrate from the bottom layer to the top layer, effectively avoiding the reverse osmosis of the exudate.
[0018] The scheme of the present invention solves the defects of traditional technology through the synergistic effect of multiple mechanisms. First, the curcumin modification not only gives the bottom layer hydrophobicity, but also provides antibacterial and antioxidant functions; secondly, the introduction of CaO2 realizes continuous in-situ oxygen supply, providing a favorable microenvironment for wound healing; thirdly, the interface design of the double-layer structure ensures good mechanical strength and avoids interlayer separation during use. This multifunctional collaborative design significantly improves the comprehensive performance of the dressing. Through material modification and structural design, a stable hydrophobic and hydrophilic gradient is established, and the directional migration of exudate is achieved. At the same time, through the precise control of process parameters, the stable performance of each functional layer is guaranteed, so that the dressing can continuously and effectively manage the wound exudate, solving the technical problem in the prior art that the water absorption performance of the diabetic wound dressing and the unidirectional exudate extraction ability are difficult to coordinate. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a flow chart of the method of the present invention.
[0020] Figure 2 This is a 20 μm electron microscope image of the composite dressing obtained in Group 1 in Example 3.
[0021] Figure 3 This is a 20 μm electron microscope image of the composite dressing obtained in Group 2 of Example 3.
[0022] Figure 4 This is a 20 μm electron microscope image of the composite dressing obtained in Group 3 of Example 3.
[0023] Figure 5 This is a 20 μm electron microscope image of the composite dressing obtained from control group 1 in Example 3. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0025] like Figure 1 FIG. 1 is a flow chart of a method for preparing a chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide provided by the present invention. The method comprises the following steps:
[0026] S01, preparing a mixed spinning solution of chitosan and polyethylene oxide, mixing chitosan with a deacetylation degree of 80 to 95% and a weight average molecular weight of 180 kilodaltons and polyethylene oxide with a viscosity average molecular weight of 600 kilodaltons in a mass ratio of 40:60 to 60:40, adding 50% by mass acetic acid and 40% by mass deionized water, and stirring at room temperature for 12 to 24 hours;
[0027] S02, using a microfluidic nano air jet spinning machine for spinning, and determining the processing parameters based on a multidimensional backpack optimization algorithm: the processing parameters include a solution advancement rate, an air pressure value, and an environmental humidity value, the solution advancement rate is 0.5 to 3.0 ml per hour, the air pressure value is 0.06 to 0.14 MPa, the environmental humidity value is 20 to 40%, so that the coefficient of variation of the uniformity of the diameter of the nanofibers in the spinning machine is less than 15%, the nozzle distance of the spinning machine is 25 to 36 cm, the receiver speed of the spinning machine is 800 to 1400 rpm, and the spinning time is 6 hours;
[0028] S03, placing the nanofibers obtained by the spinning machine in a vacuum environment at 25 degrees Celsius for 24 to 48 hours, soaking the treated nanofibers in anhydrous ethanol for 12 to 48 hours, soaking the soaked nanofibers in deionized water for 20 to 60 minutes, and freeze-drying the soaked nanofibers for 24 to 48 hours;
[0029] S04, preparing a curcumin anhydrous ethanol solution with a concentration of 25 to 100 micromoles per liter, modifying the freeze-dried nanofibers by a padding process, wherein the pressure value of the padding process is 0.5 to 2.0 MPa, the roller speed of the padding process is 0.5 to 1.5 revolutions per minute, the padding number of the padding process is 5 to 15 times, and the modified nanofibers are dried in an environment of 30±5 degrees Celsius for 10 to 30 minutes;
[0030] S05, preparing a sodium alginate solution, dissolving sodium alginate in deionized water and stirring for 8 to 12 hours to obtain a sodium alginate solution with a mass fraction of 5 to 10%;
[0031] S06, preparing a chitosan solution, dissolving chitosan having a degree of deacetylation of 87.5±7.5% and a weight average molecular weight of 180 kilodaltons in a mixture of acetic acid and deionized water at a pH of 5, and stirring for 8 to 12 hours to obtain a chitosan solution having a mass fraction of 5 to 10%;
[0032] S07, mixing the sodium alginate solution and the chitosan solution, adding glycerol accounting for 10% of the total mass of the mixed solution, adding calcium peroxide with a mass fraction of 1 to 3%, and stirring for 20 to 60 minutes to obtain a mixed solution;
[0033] S08, introducing the mixed solution into a 24-well plate and freezing it at a temperature of -20±5 degrees Celsius for 24 to 48 hours;
[0034] S09, placing the frozen mixed solution in a freeze dryer at a temperature of minus 40±10 degrees Celsius for 36 to 48 hours;
[0035] S10. Placing the dried curcumin-modified nanofibers on a bottom layer, and placing the dried calcium peroxide mixed solution on a top layer, and hot pressing for 10 to 15 minutes at a temperature of 40 to 60 degrees Celsius and a pressure of 10 to 15 MPa to obtain the double-layer diabetic wound composite dressing.
[0036] The specific implementation of the above steps is described in detail below. The specific implementation of step S01 is to prepare a mixed spinning solution of chitosan and polyethylene oxide. First, the raw materials need to be pre-treated and quality tested, the molecular weight distribution of chitosan and polyethylene oxide is measured by gel permeation chromatography, and the deacetylation degree of chitosan is measured by nuclear magnetic resonance hydrogen spectrum. After the raw material detection is qualified, chitosan and polyethylene oxide are mixed according to the set mass ratio. The determination of this mass ratio adopts orthogonal experimental design method, and the viscosity, conductivity and film-forming performance of the mixture are investigated by setting the mass ratio of different levels. In the mixing process, mechanical stirring and ultrasonic coordinated dispersion technology are adopted, and the ultrasonic power is controlled to be 200 watts, intermittent ultrasound, and the ultrasonic time and intermittent time ratio is 3 to 1, and the total processing time is 30 minutes. Subsequently, acetic acid with a mass fraction of 50% and deionized water with a mass fraction of 40% are added. The selection of this ratio is based on the solubility parameter theory, and the compatibility of the solvent and the polymer is calculated by the Hansen solubility parameter. The stirring process adopts program temperature control, stirring at 35 degrees Celsius for the first 2 hours, then cooling to room temperature and continuing stirring for 10 to 22 hours. The stirring rate adopts variable speed control, 500 revolutions per minute for the first hour, and then adjusted to 300 revolutions per minute. This stirring method can fully dissolve the polymer while avoiding shear degradation. The purpose of this step is to obtain a spinning solution with stable performance and uniform dispersion. The final viscosity of the solution should be controlled at 3000 to 5000 millipascals, the conductivity should be 2.5 to 3.5 millisieverts per centimeter, and the surface tension should be 35 to 40 millinewtons per meter.
[0037] The specific implementation of step S02 is to prepare nanofibers using microfluid nano air jet spinning technology, and this step uses a multidimensional backpack optimization algorithm to optimize the process parameters. First, a process parameter optimization model is established, and the solution advancement rate, air pressure value, and ambient humidity value are used as decision variables, the fiber diameter uniformity is used as the objective function, and the equipment capacity and process stability are used as constraints. The optimization process is solved by a dynamic programming method, the parameter space is discretized into a finite state, and the optimal parameter combination is calculated by the state transfer equation. Specifically, the solution advancement rate is divided into 25 levels within the range of 0.5 to 3.0 ml per hour, the air pressure value is divided into 20 levels within the range of 0.06 to 0.14 MPa, and the ambient humidity value is divided into 20 levels within the range of 20 to 40%. Through the recursive relationship, the objective function value under each state is calculated, and the optimal decision path is recorded. In actual operation, the equipment is first preheated to stabilize the spinneret temperature at 25 degrees Celsius and the ambient humidity reaches the set value. Start the gas compression system, and after the pressure stabilizes, start spinning. During the spinning process, an online monitoring system is used to record the fiber formation process in real time, and the fiber quality is analyzed through image processing algorithms. The process parameters are fine-tuned according to the feedback results. The purpose of this step is to obtain nanofibers with uniform diameter and smooth surface. The fiber diameter should be controlled in the range of 200 to 500 nanometers, and the coefficient of variation of diameter uniformity should be less than 15%.
[0038] The specific implementation method of step S03 is to post-process the nanofiber, and this step adopts multi-stage gradient processing technology. First, process in a vacuum environment, adopt a program temperature rise method, initially process at 20 degrees Celsius for 2 hours, then heat up to 25 degrees Celsius and continue to process for 22 to 46 hours, and the vacuum degree is maintained at 100 Pa. Then carry out solvent treatment, adopt anhydrous ethanol immersion, and the immersion process adopts a constant temperature oscillation method, the oscillation frequency is 120 times per minute, and the temperature is maintained at 30 degrees Celsius. Afterwards, deionized water is soaked, and this process adopts pH value gradient control, the initial pH value is 5, and it is adjusted once every 10 minutes, and the final pH value reaches 7. Finally, freeze drying is carried out, and a program cooling method is adopted, the initial temperature is 4 degrees Celsius, and it is reduced to minus 40 degrees Celsius at a rate of 2 degrees Celsius per hour, and then vacuum drying is carried out. The purpose of this step is to remove the residual solvent in the fiber and adjust the surface properties of the fiber. The moisture content of the fiber after treatment should be less than 1%, and the residual solvent content should be less than 100 micrograms per gram.
[0039] The specific implementation method of step S04 is to modify the nanofiber with curcumin by a padding process, and this step adopts the response surface method to optimize the process parameters. First, a curcumin solution is prepared, and an ultrasound-assisted dissolution technology is adopted, and the ultrasonic power is controlled to be 150 watts, and the processing time is 15 minutes. A double-roller rolling car is adopted in the padding process, and the optimal process parameter combination is determined by orthogonal test. The optimization of the three parameters of pressure value, roller speed, and padding number adopts the Box-Behnken experimental design, and the curcumin loading and release performance are used as the response value to establish a quadratic regression model. The significance and interaction of each factor are determined by analyzing the variance, and the optimal process parameters are solved by the gradient descent method. The purpose of this step is to achieve uniform loading and controlled release of curcumin, and the loading should reach 50 to 100 micrograms per square centimeter, and the cumulative release rate in 24 hours should be controlled at 40 to 60%.
[0040] The specific implementation method of step S05 and step S06 is to prepare sodium alginate solution and chitosan solution, and determine the optimal dissolution conditions by orthogonal experimental design method. The dissolution process of sodium alginate adopts segmented temperature control technology, dissolving at 40 degrees Celsius for the first 2 hours, and then cooling to room temperature to continue dissolving for 6 to 10 hours. The dissolution process of chitosan adopts pH gradient dissolution technology, with an initial pH value of 3, adjusted every 2 hours, and the final pH value reaches 5. The uniformity of the solution is characterized by laser scattering method, and the viscosity of the solution is measured by rheometer. The purpose of preparing the two solutions is to provide raw materials for the subsequent preparation of aerogel. The final viscosity of the solution should be controlled at 800 to 1200 milliPascal seconds, and the transmittance of the solution should be greater than 90%.
[0041] The specific implementation method of step S07 is to prepare a composite solution and optimize the mixing process using a fuzzy control algorithm. First, a sodium alginate solution and a chitosan solution are mixed according to a set ratio, and the mixing process adopts a program temperature control method, and the temperature is maintained at 25 degrees Celsius. After adding glycerol, a high shear dispersion technology is adopted, and the shear rate is 5000 revolutions per minute, and the processing time is 10 minutes. Subsequently, calcium peroxide is added, and an ultrasonic dispersion technology is adopted, and the ultrasonic power is controlled to be 180 watts, intermittent ultrasound, and the ultrasonic time and intermittent time ratio is 2 to 1. The purpose of this step is to obtain a uniform and stable composite solution, and the viscosity of the solution should be controlled at 1500 to 2000 milliPa seconds, and the dispersed particle size of calcium peroxide should be less than 1 micron.
[0042] The specific implementation method of step S08 and step S09 is to prepare aerogel by freeze-drying technology, and optimize the freeze-drying process by adaptive control algorithm. The freezing process adopts a programmed cooling method, initially dropping to minus 20 degrees Celsius at a rate of 1 degree Celsius per minute, and after keeping it for 2 hours, continue to cool to minus 40 degrees Celsius. The sublimation drying process adopts a segmented control method, maintaining the vacuum degree at 50 Pa for the initial 8 hours, then dropping to 10 Pa, and the shelf temperature increases linearly with time. The purpose of this step is to obtain aerogel with uniform porous structure. The density of the aerogel should be controlled at 0.05 to 0.08 grams per cubic centimeter, and the porosity should be greater than 90%.
[0043] The specific implementation method of step S10 is to prepare the composite dressing by hot pressing process, and optimize the hot pressing process parameters by simulated annealing algorithm. First, the material is pretreated, the nanofiber layer and the aerogel layer are placed in sequence, and the infrared preheating method is adopted to uniformly increase the material temperature to 35 degrees Celsius. The hot pressing process adopts a programmed temperature rising method, and rises to the set temperature at a rate of 2 degrees Celsius per minute. The pressure adopts a step loading method, and increases by 2 MPa every 2 minutes until the set pressure is reached. The purpose of this step is to achieve effective compounding of the two layers of material, the interlayer peel strength should be greater than 2 Newtons per centimeter, and the air permeability of the composite material should be greater than 2000 grams per square meter per 24 hours.
[0044] The algorithm or model involved in the present invention is described in detail below.
[0045] 1. The process parameter optimization model based on the multidimensional knapsack optimization algorithm in step S02 is specifically expressed as follows:
[0046]
[0047] Where F is the objective function value, indicating the uniformity of fiber diameter; v ij The payoff value of selecting the jth parameter combination for the i-th state; w ij The resource consumption of selecting the jth parameter combination for the i-th state; C j is the capacity constraint of the j-th resource; n is the number of states; m is the number of parameter combinations.
[0048] Parameter acquisition method:
[0049] v ij Calculation of fiber diameter data obtained by image processing: First, collect scanning electron microscope photos of fiber cross sections, use ImageJ software to measure the diameters of 100 fibers, and calculate the coefficient of variation; w ij Obtained through real-time data collection by equipment sensors; C j Determined according to the limit values given in the equipment manual, the upper limit of the solution advancement rate is 3.0 ml per hour, the upper limit of the air pressure value is 0.14 MPa, and the upper limit of the ambient humidity value is 40%.
[0050] 2. Fiber diameter uniformity calculation model:
[0051]
[0052] Where CV is the coefficient of variation; d i is the diameter of the ith fiber; N is the total number of measured fibers, which is taken as 100; σ is the standard deviation; μ is the average diameter.
[0053] 3. Box-Behnken response surface model of curcumin loading in step S04:
[0054]
[0055] Where, Y is the curcumin loading; X i are process parameters, including pressure value X1, roller speed X2, and padding times X3; β0 is a constant term; β i is the coefficient of the first-order term; β ii is the square term coefficient; β ij is the interaction coefficient; k is the number of factors, and its value is 3; ∈ is the random error term.
[0056] Parameter acquisition method:
[0057] Y was determined by ultraviolet spectrophotometer to establish a standard curve of curcumin, with a measurement wavelength of 425 nanometers; X i The value range of is: X1 is 0.5 to 2.0 MPa, X2 is 0.5 to 1.5 rpm, and X3 is 5 to 15 times; the coefficients are obtained by least squares fitting.
[0058] 4. Rheological model of the composite solution in step S07:
[0059]
[0060] Wherein, η is the apparent viscosity; K is the consistency coefficient; γ is the shear rate; n is the flow index; E is the activation energy; R is the gas constant, 8.314 joules per mole; and T is the absolute temperature.
[0061] Parameter acquisition method:
[0062] η was measured by rotational rheometer with a shear rate range of 0.1 to 100 s and a temperature of 25 °C; K and n were obtained by nonlinear fitting of the experimental data; and E was calculated by measuring the apparent viscosity at different temperatures.
[0063] 5. Heat and mass transfer model of freeze drying process in steps S08 and S09:
[0064]
[0065] Where, T is temperature; t is time; α is thermal diffusion coefficient; M is moisture content; D eff is the effective diffusion coefficient; x, y, z are the spatial coordinates.
[0066] Parameter acquisition method:
[0067] T is monitored in real time by a temperature sensor; α is measured by a thermal conductivity meter; M is measured by a gravimetric method; D eff Obtained by fitting the drying curve.
[0068] 6. Calculation model of interlayer bonding strength in step S10:
[0069]
[0070] Wherein, σ is the interlayer bonding strength; F is the peeling force; w is the specimen width; M is the bending moment; I is the moment of inertia; and y is the distance from the neutral axis.
[0071] Parameter acquisition method:
[0072] F is measured by a peel strength tester with a tensile speed of 100 mm / min; w is taken as 25 mm; M, I, and y are calculated based on the sample size.
[0073] 1. The process of derivation and establishment of the process parameter optimization model of the multi-dimensional backpack optimization algorithm is described in detail as follows:
[0074] First, an initial single-objective optimization model is constructed, and fiber diameter uniformity is considered as the optimization target. Due to the coupling relationship between process parameters, the concept of state transfer is introduced to transform the problem into a multi-stage decision-making process. The specific derivation steps are as follows:
[0075] Step 1: Discretize the continuous parameter space, and divide the solution propulsion rate, air pressure value, and ambient humidity value into 25, 20, and 20 levels respectively;
[0076] Step 2: Establish the benefit function of parameter combination in the form of weighted summation, with the weight of fiber diameter uniformity being 0.5, the weight of fiber morphology integrity being 0.3, and the weight of process stability being 0.2;
[0077] Step 3: Consider equipment constraints and establish a resource consumption function, including three dimensions: energy consumption, material consumption, and time consumption;
[0078] Step 4: Use the recursive equation to solve the optimal parameter combination.
[0079] The innovation of this model is to transform the optimization problem of multiple process parameters into a combinatorial optimization problem with constraints, which can effectively avoid local optimal solutions.
[0080] 2. The derivation and establishment process of the fiber diameter uniformity calculation model is described in detail as follows:
[0081] Based on statistical principles, the discrete degree of fiber diameter distribution is considered. The derivation steps are as follows:
[0082] Step 1: Collect fiber diameter data and measure the diameters of 100 fibers using a scanning electron microscope;
[0083] Step 2: Calculate the sample mean as the representative value of fiber diameter;
[0084] Step 3: Calculate the standard deviation to characterize the degree of fluctuation of fiber diameter;
[0085] Step 4: Introduce the coefficient of variation to eliminate the impact of dimension.
[0086] The characteristic of this model is that it can accurately reflect the distribution characteristics of fiber diameter and facilitate comparison between batches.
[0087] 3. Construction process of Box-Behnken response surface model:
[0088] The response surface methodology was used to optimize the curcumin loading process, and the derivation steps were as follows:
[0089] Step 1: Select the factor level, and take 3 levels for each of pressure value, roller speed, and padding times;
[0090] Step 2: Design an orthogonal experimental scheme with 15 experimental points in total;
[0091] Step 3: Conduct variance analysis to screen significant factors;
[0092] Step 4: Establish a quadratic polynomial regression equation.
[0093] The parameter coefficients are obtained in the following way:
[0094]
[0095] Where N is the number of experiments; Y i is the response value of the ith experiment; X ij is the coded value of the jth factor in the i-th experiment.
[0096] 4. The process of establishing the rheological model of composite solution:
[0097] Based on the non-Newtonian fluid theory, the effects of temperature and shear rate are considered. The derivation steps are as follows:
[0098] Step 1: Establish a power law model to describe the relationship between shear rate and apparent viscosity;
[0099] Step 2: Introduce the Arrhenius equation to consider the effect of temperature on viscosity;
[0100] Step 3: Determine model parameters through experimental data.
[0101] This model can accurately predict the rheological behavior of solutions under different process conditions.
[0102] 5. Derivation of heat and mass transfer model for freeze drying process:
[0103] Based on Fourier's law and Fick's law, a set of partial differential equations is established. The derivation steps are as follows:
[0104] Step 1: Analyze the system boundary conditions, including initial temperature distribution and moisture distribution;
[0105] Step 2: Consider the latent heat effect during phase change;
[0106] Step 3: Introduce the effective diffusion coefficient to simplify the complex mass transfer process;
[0107] Step 4: Solve the system of equations using the finite difference method.
[0108] The model can simulate the changes in temperature and concentration fields during freeze-drying.
[0109] 6. Derivation of interlayer bonding strength calculation model:
[0110] Based on the principle of material mechanics, the composite stress state during the peeling process is considered. The derivation steps are as follows:
[0111] Step 1: Analyze the stress during the peeling process;
[0112] Step 2: Establish a superposition model of axial stress and bending stress;
[0113] Step 3: Consider the influence of geometric parameters.
[0114] This model can accurately evaluate the interlayer bonding performance of composite materials.
[0115] Specifically, the principle of the present invention is: the double-layer composite dressing of the present invention realizes the directional migration of exudate based on the capillary effect and the surface energy gradient principle. After the bottom nanofiber is modified by curcumin, its surface energy is significantly reduced to form a hydrophobic interface; while the top aerogel has a porous structure and hydrophilicity, which can generate a strong capillary force. This gradient difference in surface energy drives the exudate to migrate from the hydrophobic layer to the hydrophilic layer. At the same time, the slow release decomposition of CaO2 in the aerogel layer produces oxygen to form tiny bubbles, which further promote the upward movement of the liquid during the rising process. In the preparation process of the composite dressing, the spinning parameters are accurately controlled by the multidimensional backpack optimization algorithm to ensure the uniformity and hydrophobicity of the nanofibers; the curcumin loading process is optimized by the Box-Behnken response surface method to achieve the controllability of the surface modification; the aerogel preparation parameters are adjusted by the fuzzy control algorithm to ensure the stability of its porous structure. The coordinated application of these algorithms enables the various performance indicators of the double-layer structure to reach the optimal ratio.
[0116] A specific embodiment 1 of the present invention is provided below, and the specific implementation method of each step in this embodiment 1 is described in detail as follows.
[0117] The specific implementation of step S01 is to prepare a mixed spinning solution of chitosan and polyethylene oxide, firstly determine the molecular weight distribution of the raw materials by gel permeation chromatography, and determine the deacetylation degree of chitosan by nuclear magnetic resonance hydrogen spectroscopy. After the raw materials are qualified, the mass ratio is determined according to the orthogonal experimental design method, and the viscoelastic theory is used to establish a mixture performance prediction model: Where η * is the complex viscosity of the mixture, and are the complex viscosities of chitosan and polyethylene oxide, respectively, φ1 and φ2 are the volume fractions of each component, and K is the interaction coefficient. The model is used to optimize the mixing ratio and obtain the best film-forming performance. Mechanical stirring and ultrasonic synergistic dispersion technology are used in the mixing process, with an ultrasonic power of 200 watts, intermittent ultrasound, and a total processing time of 30 minutes. Acetic acid and deionized water are then added, and the solvent ratio is determined based on the solubility parameter theory: In the formula, R a is the solubility parameter distance, δ d , δ p , δ h The stirring process is controlled by programmed temperature, with stirring at 35 degrees Celsius for the first 2 hours, followed by continued stirring at room temperature. The purpose of this step is to obtain a spinning solution with stable performance, and the final viscosity should be controlled at 3000 to 5000 mPas.
[0118] The specific implementation of step S02 is to determine the processing parameters through a multi-dimensional knapsack optimization algorithm. First, a process parameter optimization model is established: In the formula, F is the objective function value, v ij is the return value of the parameter combination, x ij is the decision variable. In order to improve the optimization efficiency, a dynamic programming strategy is adopted to discretize the parameter space: k (s k )=max{v k (a k )+f k+1 (s k+1 )}, where f k (s k ) is the optimal value function of the kth stage, v k (a k ) is decision a k The optimal parameter combination is solved by recursion. In actual operation, the equipment is first preheated to stabilize the temperature of the spinneret at 25 degrees Celsius and the ambient humidity reaches the set value. Start the gas compression system and start spinning after the pressure stabilizes. An online monitoring system is used during the spinning process, and the image processing algorithm analyzes the fiber quality in real time: Q = w1D + w2U + w3S, where Q is the comprehensive quality index, D is the diameter uniformity, U is the orientation degree, S is the surface defect rate, and w1, w2, and w3 are weight coefficients. Fine-tune the process parameters based on the feedback results to ensure uniform fiber diameter and smooth surface.
[0119] The specific implementation of step S03 is to post-treat the nanofibers using a multi-level gradient treatment technology. First, treat in a vacuum environment and establish a solvent volatilization kinetic model: In the formula, c is the solvent concentration, t is the time, k1 and k2 are rate constants, n is the reaction order, and c s is the surface solvent concentration. The treatment process adopts a programmed temperature rise method, and the temperature change conforms to the exponential temperature rise law: T = T0 + (T m -T0)(1-e -βt ), where T0 is the initial temperature, T m is the final temperature, and β is the heating rate coefficient. Solvent treatment is then carried out, using anhydrous ethanol for immersion. The mass transfer mechanism of the immersion process can be expressed as: Where J is the mass transfer flux, D is the diffusion coefficient, is the concentration gradient, and v is the convection velocity. The oscillation process can be described by the resonance equation: Where x is the displacement, ξ is the damping ratio, ω0 is the natural frequency, and F(t) is the external force.
[0120] The specific implementation of step S04 is to modify the nanofibers with curcumin by a padding process. The process parameters are optimized by using the Box-Behnken response surface method: The adsorption process of curcumin on the fiber surface can be described by the Langmuir adsorption isotherm: In the formula, q e is the equilibrium adsorption amount, q m is the maximum adsorption capacity, K L is the adsorption equilibrium constant, c e is the equilibrium concentration. The pressure distribution during the padding process can be calculated using the Hertz contact theory: Where p(x) is the pressure distribution function, p0 is the maximum pressure, and a is the contact half width. The release kinetics of curcumin is described by the Peppas equation: Where M t is the release amount at time t, M ∞ is the theoretical maximum release amount, k is the release rate constant, and n is the release index.
[0121] The specific implementation of step S05 and step S06 is to prepare sodium alginate solution and chitosan solution. The mixing efficiency during the solution preparation process can be characterized by the power number: Where N P is the power number, P is the input power, ρ is the density, n is the speed, and d is the diameter of the stirring paddle. The uniformity of the solution is characterized by laser scattering technology, and the particle size distribution function is: Where D is the particle size, D g is the geometric mean particle size, σ g is the geometric standard deviation. The rheological properties of the solution are described by the generalized non-Newtonian fluid model: τ = Kγ n +τ0, where τ is the shear stress, K is the consistency index, γ is the shear rate, n is the flow index, and τ0 is the yield stress.
[0122] The specific implementation of step S07 is to prepare a composite solution. This step uses a fuzzy control algorithm to optimize the mixing process. First, a basic fuzzy control system is constructed, and its core fuzzy rule is: R i : In the formula, x1 and x2 are input variables, representing the real-time monitoring values of temperature and viscosity respectively, and y is the output variable, representing the adjustment amount of the stirring rate. B i is the corresponding fuzzy set. The stirring efficiency in the mixing process is characterized by the mixing index: Where MI is the mixing index, σ 2 is the current mixture concentration variance, is the variance of the initial mixture concentration.
[0123] When the sodium alginate solution and the chitosan solution are mixed in a set ratio, the temperature is kept constant at 25 degrees Celsius by program temperature control. After adding glycerol, high shear dispersion technology is used, and the rheological properties of the shear process are described by the non-Newtonian fluid model: In the formula, τ is the shear stress, K is the consistency index, is the shear rate, n is the flow index, the rotation speed of high shear dispersion is 5000 rpm, and the processing time is 10 minutes.
[0124] Then calcium peroxide was added and ultrasonic dispersion technology was used. The sound field distribution during the ultrasonic process can be expressed as: p(t) = p A sin(2πft), where p A is the sound pressure amplitude, and f is the frequency. The ultrasonic power is controlled at 180 watts, and intermittent ultrasonic method is used, with the ratio of ultrasonic time to intermittent time being 2 to 1. The stability of the dispersed system is characterized by Zeta potential, and its absolute value is controlled to be greater than 30 mV. The stirring process adopts a variable speed control strategy, with high-speed stirring initially used to promote dispersion, and the speed is reduced in the later stage to maintain uniformity, so as to obtain a uniform and stable composite solution. The final viscosity of the solution should be controlled at 1500 to 2000 mPas, and the dispersed particle size of calcium peroxide should be less than 1 micron. This step ensures the uniformity and stability of the composite solution by precisely controlling the process parameters, laying the foundation for the subsequent aerogel preparation.
[0125] The specific implementation of step S08 and step S09 is to prepare aerogel by freeze drying technology, and optimize the freeze drying process by using an adaptive control algorithm. The heat and mass transfer process during the freezing process can be described by a group of partial differential equations: The ice crystal growth dynamics can be described by the modified Johnson-Mehl-Avrami equation: X(t) = 1-exp(-Kt n ), where X(t) is the crystallinity, K is the rate constant, and n is the reaction order. The mass transfer flux of the vacuum sublimation process can be expressed as: Where K is the mass transfer coefficient, A is the mass transfer area, M is the molecular weight, and p i and p f are the interface pressure and the system pressure respectively. The heat transfer during the sublimation process can be described by Fourier's law: Where q is the heat flux density and k is the thermal conductivity. The pore structure of aerogel can be characterized by fractal theory: N(r) = cr -D , where N(r) is the number of pores with a size greater than r, c is the proportionality coefficient, and D is the fractal dimension.
[0126] The specific implementation of step S10 is to prepare the composite dressing by hot pressing process. The heat transfer process during hot pressing can be described by the non-steady-state heat conduction equation: Where ρ is the density, c p is the specific heat capacity, and λ is the thermal conductivity. The pressure distribution is analyzed by nonlinear finite element analysis: [K]{u}={F}, where [K] is the stiffness matrix, {u} is the displacement vector, and {F} is the load vector. The interlayer bonding strength can be described by the viscoelastic constitutive equation: Where σ(t) is stress, E(t) is relaxation modulus, and ε is strain. The simulated annealing algorithm is used to optimize the hot pressing process parameters, and the objective function is: f(x) = w1σ b +w2σ p +w3P, where σ b is the interlayer bonding strength, σ p is the peel strength, P is the air permeability, and w1, w2, and w3 are weight coefficients.
[0127] The quality control in the whole preparation process adopts the statistical process control method, and the control chart is established: UCL = μ + 3σ, LCL = μ - 3σ, where UCL and LCL are the upper and lower control limits, μ is the mean, and σ is the standard deviation. The process capability index can be expressed as: In the formula, USL and LSL are the upper and lower limits of the specification, respectively. The product performance evaluation adopts the grey correlation analysis method, and the correlation coefficient calculation formula is: In the formula, x0(k) is the reference sequence, x i (k) is the comparison sequence and ρ is the resolution coefficient.
[0128] The optimization process of each process parameter adopts genetic algorithm, and chromosome coding adopts real number coding: chromosome = [gene1, gene2, ..., gene n ], the fitness function is: Where P i is the performance index, w i is the weight coefficient. The crossover operation uses arithmetic crossover: x new =αx1+(1-α)x2, where x new is a new individual, x1 and x2 are parent individuals, and α is a random number. The mutation operation uses non-uniform mutation: In the formula, x max is the upper bound, t is the current generation, T is the maximum generation, and b is the shape parameter. The optimal process parameter combination is obtained through iterative optimization to achieve comprehensive optimization of product performance.
[0129] In order to better understand and implement the present invention, the following provides Example 2 of a specific application scenario of the present invention:
[0130] In the process of developing a new diabetic wound dressing, a research and development team used the method of the present invention to prepare a double-layer composite dressing with a unidirectional moisture conduction function. The specific implementation steps are as follows:
[0131] First, a chitosan and polyethylene oxide mixed spinning solution was prepared. Chitosan with a deacetylation degree of 85% and a weight average molecular weight of 180 kilodaltons was selected and mixed with polyethylene oxide with a viscosity average molecular weight of 600 kilodaltons in a mass ratio of 50:50, 50% acetic acid by mass and 40% deionized water by mass were added, and stirred at room temperature for 18 hours to obtain a uniform spinning solution with a viscosity of 4200 millipascals and a conductivity of 3.0 millisieverts per centimeter.
[0132] A microfluidic nano-air jet spinning machine was used for spinning, and the process parameters were optimized by a multi-dimensional backpack optimization algorithm. After calculation, it was finally determined that the solution propulsion rate was 2.0 ml per hour, the air pressure value was 0.10 MPa, the ambient humidity value was 30%, the nozzle distance was 30 cm, the receiver speed was 1200 rpm, and the spinning time was 6 hours. An online monitoring system was used during the spinning process to monitor the fiber formation in real time.
[0133] The prepared nanofibers were placed in a vacuum environment at 25 degrees Celsius for 36 hours, then soaked in anhydrous ethanol for 24 hours, then soaked in deionized water for 40 minutes, and finally freeze-dried for 36 hours. Scanning electron microscopy showed that the fiber diameter was distributed between 300 and 400 nanometers, and the coefficient of variation of the diameter uniformity was 12%.
[0134] A curcumin anhydrous ethanol solution with a concentration of 75 micromoles per liter was prepared, and the nanofibers were modified by a padding process. The pressure value of the padding process was 1.5 MPa, the roller speed was 1.0 rpm, the number of padding was 10 times, and the modified nanofibers were dried in an environment of 30±5 degrees Celsius for 20 minutes. Through the contact angle test, the water contact angle of the modified fiber membrane was 135 degrees.
[0135] When preparing the aerogel layer, sodium alginate is first dissolved in deionized water and stirred for 10 hours to obtain a sodium alginate solution with a mass fraction of 8%. At the same time, chitosan with a deacetylation degree of 87.5% is dissolved in a mixture of acetic acid and deionized water with a pH value of 5 and stirred for 10 hours to obtain a chitosan solution with a mass fraction of 8%. The two solutions are mixed in a volume ratio of 1:1, glycerol accounting for 10% of the total mass of the mixed solution is added, and calcium peroxide with a mass fraction of 2% is continuously added, and stirred for 40 minutes to obtain a uniform mixed solution.
[0136] The mixed solution was introduced into a 24-well plate and frozen at a temperature of minus 20 ± 5 degrees Celsius for 36 hours, and then the frozen sample was placed in a freeze dryer at a temperature of minus 40 ± 10 degrees Celsius for 42 hours. According to the porosity test, the porosity of the aerogel reached 95% and the specific surface area was 120 square meters per gram.
[0137] Finally, the curcumin modified nanofibers were placed on the bottom layer and the calcium peroxide aerogel was placed on the top layer, and hot pressed for 12 minutes at a temperature of 50 degrees Celsius and a pressure of 12 MPa to obtain a double-layer composite dressing. The product performance test results are shown in Table 1 below:
[0138] Table 1 Product performance test table
[0139] Test items Test Results Test Method Liquid absorption rate 15 grams per gram Weighing method Breathability 2500 g / m2 / 24 hours Moisture cup method Interlayer peel strength 2.8 Newton per centimeter Peel test Antibacterial rate 99.9% Plate counting method Oxygen release duration 72 hours Dissolved oxygen meter One-way moisture conduction ratio 8.5 Moisture conductivity test
[0140] For the management of diabetic wound exudate, traditional methods mainly use single-layer highly absorbent dressings or multi-layer composite dressings. Although single-layer highly absorbent dressings have strong water absorption properties, they cannot achieve directional migration of exudate, which easily causes wound maceration. Although multi-layer composite dressings can improve exudate management to a certain extent, the bonding between layers is unstable and the preparation process is complicated. The present invention successfully achieves unidirectional conduction of exudate by designing a double-layer structure of a hydrophobic bottom layer and a hydrophilic top layer. The liquid absorption rate reaches 15 grams per gram, and the unidirectional moisture conduction ratio reaches 8.5, which is significantly better than traditional dressings. At the same time, the preparation process of the present invention adopts a variety of optimization algorithms to control parameters, which significantly improves the stability and repeatability of product performance, and provides reliable technical support for the large-scale production of diabetic wound dressings.
[0141] In clinical trials, the composite dressing prepared by the present invention showed excellent results in wound treatment of 10 patients with diabetic foot. The dressing can effectively absorb wound exudate, maintain a suitable moist environment for the wound, and improve the hypoxic state of the wound by continuous oxygen release. After 4 weeks of treatment, the wound healing rate reached 85%, which was significantly higher than the 65% healing rate of the control group using traditional dressings. Patient satisfaction surveys show that the dressing of the present invention has received high evaluations in terms of wearing comfort and convenience of replacement. These results fully demonstrate the significant advantages of the present invention in solving the management of diabetic wound exudate.
[0142] Compared with the traditional technology, the innovation of this embodiment is mainly reflected in the following aspects: first, the controllable hydrophobicity of nanofibers is achieved through curcumin modification, second, calcium peroxide is introduced to achieve continuous oxygen release function, and third, multiple optimization algorithms are used to ensure accurate control of the preparation process. These innovations enable the present invention to not only solve the problem of unidirectional exudate extraction, but also give the dressing multiple functions such as antibacterial and healing promotion, providing a new solution for the treatment of diabetic wounds.
[0143] In order to better understand and implement the present invention, the following provides an embodiment 3 of the present invention including multiple implementation groups and a comparison group, which is used to select a more optimized ratio for the products obtained by different methods:
[0144] Implementation group 1: The chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide is composed of chitosan, sodium alginate and calcium peroxide, wherein the content of chitosan is 82.5%, the content of sodium alginate is 16.5%, and the content of calcium peroxide is 1%; its preparation method is: sodium alginate is dissolved in deionized water and stirred for 8 hours to obtain a sodium alginate solution with a concentration of 10wt.%, chitosan is dissolved in a mixed solution of acetic acid and deionized water with a pH value of 5 and stirred for 8 hours to obtain a chitosan solution with a concentration of 10wt.%; after mixing the sodium alginate solution and the chitosan solution evenly, glycerol is added, and then calcium peroxide is added, and stirring is continued for 20 minutes. After stirring evenly, the mixture is introduced into a 24-well plate, placed in a refrigerator at -20±5℃ and frozen for 24 hours, and then placed in a freeze dryer at -40±10℃ and freeze-dried for 48 hours to obtain the chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide. The chitosan has a deacetylation degree of 87.5±7.5% and a weight average molecular weight of 180 kDa. The amount of glycerol added is 10 wt.% of the total amount of the sodium alginate solution and the chitosan solution.
[0145] The curcumin-loaded chitosan-based antibacterial and antioxidant nanofiber cotton dressing is composed of chitosan and polyethylene oxide, wherein the content of chitosan is 60% and the content of polyethylene oxide is 40%; the preparation method is as follows: chitosan and polyethylene oxide are dissolved in deionized water and acetic acid, and stirred for 12 hours to completely dissolve CS and PEO, wherein the content of chitosan is 6wt.%, the content of polyethylene oxide is 6wt.%, the content of acetic acid is 50wt.%, and the content of deionized water is 40wt.%. A microfluid nano air jet spinning machine is used for spinning, and after the spinning solution is injected into a 10mL syringe, a 20G needle (inner diameter 0.60mm, outer diameter 0.91mm) is used to carry out SBS at a solution propulsion rate of 1.0mL / h, an air pressure of 0.12MPa and a humidity of 20-40%. The nozzle is 36 cm away from the receiver, the receiver is 30 cm wide and 67 cm long, and runs at a speed of 1400 rpm. The spinning time of all samples was kept at 6 hours. The prepared nanofiber samples were treated in a vacuum environment at 25°C for 24 hours to remove acetic acid and excess water. Then, the obtained CS / PEO nanofibers were soaked in anhydrous ethanol for 48 hours. After that, the samples were soaked in deionized water for 20 minutes and finally freeze-dried for 24 hours. Curcumin was dissolved in anhydrous ethanol to prepare a curcumin solution with a concentration of 100 μmol / L. First, the chitosan-based nanofibers were modified with turmeric using a padding process, in which the pressure was 1.5 MPa, the roller speed was 0.5 rpm, and the number of padding times was 5 times. Then the film was placed in an oven at 30°C and dried for 10 minutes. The deacetylation degree of the chitosan is 80-95%, and the weight average molecular weight is 180 kDa; the viscosity average molecular weight of polyethylene oxide is 600 kDa;
[0146] Implementation group 2: The chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide is composed of chitosan, sodium alginate and calcium peroxide, wherein the content of chitosan is 82.5%, the content of sodium alginate is 16.5%, and the content of calcium peroxide is 1%; its preparation method is: sodium alginate is dissolved in deionized water and stirred for 8 hours to obtain a sodium alginate solution with a concentration of 10wt.%, chitosan is dissolved in a mixture of acetic acid and deionized water with a pH value of 5 and stirred for 8 hours to obtain a chitosan solution with a concentration of 10wt.%; after mixing the sodium alginate solution and the chitosan solution evenly, glycerol is added, and then calcium peroxide is added, and stirring is continued for 20 minutes. After stirring evenly, the mixture is introduced into a 24-well plate, placed in a refrigerator at -20±5℃ and frozen for 24 hours, and then placed in a freeze dryer at -40±10℃ and freeze-dried for 48 hours to obtain the chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide. The chitosan has a deacetylation degree of 87.5±7.5% and a weight average molecular weight of 180 kDa. The amount of glycerol added is 10 wt.% of the total amount of the sodium alginate solution and the chitosan solution.
[0147] The curcumin-loaded chitosan-based antibacterial and antioxidant nanofiber cotton dressing is composed of chitosan and polyethylene oxide, wherein the content of chitosan is 60% and the content of polyethylene oxide is 40%; the preparation method is as follows: chitosan and polyethylene oxide are dissolved in deionized water and acetic acid, and stirred for 12 hours to completely dissolve CS and PEO, wherein the content of chitosan is 6wt.%, the content of polyethylene oxide is 6wt.%, the content of acetic acid is 50wt.%, and the content of deionized water is 40wt.%. A microfluid nano air jet spinning machine is used for spinning, and after the spinning solution is injected into a 10mL syringe, a 20G needle (inner diameter 0.60mm, outer diameter 0.91mm) is used to carry out SBS at a solution propulsion rate of 1.0mL / h, an air pressure of 0.12MPa and a humidity of 20-40%. The nozzle is 36 cm away from the receiver, the receiver is 30 cm wide and 67 cm long, and runs at a speed of 1400 rpm. The spinning time of all samples was kept at 6 hours. The prepared nanofiber samples were treated in a vacuum environment at 25°C for 24 hours to remove acetic acid and excess water. Then, the obtained CS / PEO nanofibers were soaked in anhydrous ethanol for 48 hours. After that, the samples were soaked in deionized water for 20 minutes and finally freeze-dried for 24 hours. Curcumin was dissolved in anhydrous ethanol to prepare a curcumin solution with a concentration of 100 μmol / L. First, the chitosan-based nanofibers were modified with turmeric using a padding process, in which the pressure was 1.5 MPa, the roller speed was 0.5 rpm, and the number of padding times was 10 times. Then, the film was placed in a 30°C oven and dried for 10 minutes. The deacetylation degree of the chitosan is 80-95%, and the weight average molecular weight is 180 kDa; the viscosity average molecular weight of polyethylene oxide is 600 kDa;
[0148] Implementation group 3: The chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide is composed of chitosan, sodium alginate and calcium peroxide, wherein the content of chitosan is 82.5%, the content of sodium alginate is 16.5%, and the content of calcium peroxide is 1%; its preparation method is: sodium alginate is dissolved in deionized water and stirred for 8 hours to obtain a sodium alginate solution with a concentration of 10wt.%, chitosan is dissolved in a mixture of acetic acid and deionized water with a pH value of 5 and stirred for 8 hours to obtain a chitosan solution with a concentration of 10wt.%; after mixing the sodium alginate solution and the chitosan solution evenly, glycerol is added, and then calcium peroxide is added, and stirring is continued for 20 minutes. After stirring evenly, the mixture is introduced into a 24-well plate, placed in a refrigerator at -20±5℃ and frozen for 24 hours, and then placed in a freeze dryer at -40±10℃ and freeze-dried for 48 hours to obtain the chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide. The chitosan has a deacetylation degree of 87.5±7.5% and a weight average molecular weight of 180 kDa. The amount of glycerol added is 10 wt.% of the total amount of the sodium alginate solution and the chitosan solution.
[0149] The curcumin-loaded chitosan-based antibacterial and antioxidant nanofiber cotton dressing is composed of chitosan and polyethylene oxide, wherein the content of chitosan is 60% and the content of polyethylene oxide is 40%; the preparation method is as follows: chitosan and polyethylene oxide are dissolved in deionized water and acetic acid, and stirred for 12 hours to completely dissolve CS and PEO, wherein the content of chitosan is 6wt.%, the content of polyethylene oxide is 6wt.%, the content of acetic acid is 50wt.%, and the content of deionized water is 40wt.%. A microfluid nano air jet spinning machine is used for spinning, and after the spinning solution is injected into a 10mL syringe, a 20G needle (inner diameter 0.60mm, outer diameter 0.91mm) is used to carry out SBS at a solution propulsion rate of 1.0mL / h, an air pressure of 0.12MPa and a humidity of 20-40%. The nozzle is 36 cm away from the receiver, the receiver is 30 cm wide and 67 cm long, and runs at a speed of 1400 rpm. The spinning time of all samples was kept at 6 hours. The prepared nanofiber samples were treated in a vacuum environment at 25°C for 24 hours to remove acetic acid and excess water. Then, the obtained CS / PEO nanofibers were soaked in anhydrous ethanol for 48 hours. After that, the samples were soaked in deionized water for 20 minutes and finally freeze-dried for 24 hours. Curcumin was dissolved in anhydrous ethanol to prepare a curcumin solution with a concentration of 100 μmol / L. First, the chitosan-based nanofibers were modified with turmeric using a padding process, in which the pressure was 1.5 MPa, the roller speed was 0.5 rpm, and the number of padding times was 15 times. Then, the film was placed in a 30°C oven and dried for 10 minutes. The deacetylation degree of the chitosan is 80-95%, and the weight average molecular weight is 180 kDa; the viscosity average molecular weight of polyethylene oxide is 600 kDa;
[0150] Comparative group 1: The chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide is composed of chitosan, sodium alginate and calcium peroxide, wherein the content of chitosan is 82.5%, the content of sodium alginate is 16.5%, and the content of calcium peroxide is 1%. The preparation method is as follows: sodium alginate is dissolved in deionized water and stirred for 8 hours to obtain a sodium alginate solution with a concentration of 10wt.%, chitosan is dissolved in a mixture of acetic acid and deionized water with a pH value of 5 and stirred for 8 hours to obtain a chitosan solution with a concentration of 10wt.%; sodium alginate solution and chitosan solution are mixed evenly, glycerol is added, and then calcium peroxide is added, stirring is continued for 20 minutes, and after stirring evenly, it is introduced into a 24-well plate, placed in a refrigerator at -20±5℃ and frozen for 24 hours, and then placed in a freeze dryer at -40±10℃ and freeze-dried for 48 hours to obtain a chitosan-based oxygen-releasing antibacterial aerogel dressing loaded with calcium peroxide. The chitosan has a deacetylation degree of 87.5±7.5% and a weight average molecular weight of 180 kDa. The amount of glycerol added is 10 wt.% of the total amount of the sodium alginate solution and the chitosan solution.
[0151] The curcumin-loaded chitosan-based antibacterial and antioxidant nanofiber cotton dressing is composed of chitosan and polyethylene oxide, wherein the content of chitosan is 60% and the content of polyethylene oxide is 40%; the preparation method is as follows: chitosan and polyethylene oxide are dissolved in deionized water and acetic acid, and stirred for 12 hours to completely dissolve CS and PEO, wherein the content of chitosan is 6wt.%, the content of polyethylene oxide is 6wt.%, the content of acetic acid is 50wt.%, and the content of deionized water is 40wt.%. A microfluid nano air jet spinning machine is used for spinning, and after the spinning solution is injected into a 10mL syringe, a 20G needle (inner diameter 0.60mm, outer diameter 0.91mm) is used to carry out SBS at a solution propulsion rate of 1.0mL / h, an air pressure of 0.12MPa and a humidity of 20-40%. The nozzle is 36 cm away from the receiver, the receiver is 30 cm wide and 67 cm long, and runs at a speed of 1400 rpm. The spinning time of all samples was kept at 6 h. The prepared nanofiber samples were treated in a vacuum environment at 25 °C for 24 h to remove acetic acid and excess water. Then, the obtained CS / PEO nanofibers were soaked in anhydrous ethanol for 48 h. After that, the samples were soaked in deionized water for 20 min and finally freeze-dried for 24 h. The final electron microscope image is as follows Figures 2 to 5 As shown, the obtained data are shown in Figure 2-7.
[0152] Table 2 Porosity statistics
[0153] project Comparison group 1 Implementation Group 1 Implementation Group 2 Implementation Group 3 Porosity (%) 88.2 79.4 70.5 58.1
[0154] Table 3 Antibacterial data table
[0155]
[0156]
[0157] Table 4 Antioxidant data table
[0158] project Comparison group 1 Implementation Group 1 Implementation Group 2 Implementation Group 3 DPPH clearance rate (%) 90.6 92.4 96.1 98.6
[0159] Table 5 Cell activity data table
[0160] Time (day) / cell proliferation rate (%) Comparison group 1 Implementation Group 1 Implementation Group 2 Implementation Group 3 1 1.08 1.22 1.29 1.55 3 1.24 1.54 1.79 2.02 5 1.41 1.84 1.95 2.61
[0161] Table 6 Wound healing rate data table
[0162] Time (day) / wound healing rate (%) Comparison group 1 Implementation Group 1 Implementation Group 2 Implementation Group 3 0 0 0 0 0 3 20.80 28.70 39.55 46.28 6 59.36 66.65 71.73 74.55 10 82.41 87.12 88.67 93.82 15 90.89 93.42 96.19 98.73
[0163] Table 7 Protein deposition rate data table
[0164]
[0165] It should be noted that the variables involved in the present invention are explained in detail as shown in Table 8 below.
[0166]
[0167]
[0168] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a chitosan-based double-layer diabetic wound composite dressing loaded with curcumin and calcium peroxide, characterized in that: The following steps are involved: A mixed spinning solution of chitosan and polyethylene oxide was prepared, nanofibers were prepared by microfluidic nano-air jet spinning technology, processing parameters were determined by a multi-dimensional backpack optimization algorithm, and curcumin was loaded by a padding process after immersion treatment; A sodium alginate solution and a chitosan solution are prepared, calcium peroxide is added to prepare a mixed solution, and aerogel is prepared by a freeze-drying process; curcumin-modified nanofibers are placed on a bottom layer, and calcium peroxide aerogel is placed on a top layer for hot-pressing and compounding to obtain the double-layer diabetic wound composite dressing.
2. The preparation method according to claim 1, characterized in that: The step of preparing a mixed spinning solution is specifically to mix chitosan with a deacetylation degree of 80 to 95% and a weight average molecular weight of 180 kilodaltons and polyethylene oxide with a viscosity average molecular weight of 600 kilodaltons in a mass ratio of 40:60 to 60:40, add acetic acid with a mass fraction of 50% and deionized water with a mass fraction of 40%, and stir at room temperature for 12 to 24 hours.
3. The preparation method according to claim 1, characterized in that: The step of using a multidimensional backpack optimization algorithm to determine the processing parameters is specifically to set the solution advancement rate to 0.5 to 3.0 ml per hour, the air pressure value to 0.06 to 0.14 MPa, the ambient humidity value to 20 to 40%, the nozzle distance of the spinning machine to 25 to 36 cm, the receiver speed of the spinning machine to 800 to 1400 revolutions per minute, and the spinning time to 6 hours.
4. The preparation method according to claim 1, characterized in that: The nanofiber soaking treatment step specifically includes placing the nanofiber in a vacuum environment at 25 degrees Celsius for 24 to 48 hours, soaking the treated nanofiber in anhydrous ethanol for 12 to 48 hours, soaking the soaked nanofiber in deionized water for 20 to 60 minutes, and freeze-drying the soaked nanofiber for 24 to 48 hours.
5. The preparation method according to claim 1, characterized in that: The step of loading curcumin by the padding process specifically comprises preparing a curcumin anhydrous ethanol solution with a concentration of 25 to 100 micromoles per liter, the pressure value of the padding process is 0.5 to 2.0 MPa, the roller speed of the padding process is 0.5 to 1.5 revolutions per minute, the padding times of the padding process is 5 to 15 times, and the modified nanofibers are dried in an environment of 30±5 degrees Celsius for 10 to 30 minutes.
6. The preparation method according to claim 1, characterized in that: The step of preparing the sodium alginate solution is specifically to dissolve the sodium alginate in deionized water and stir for 8 to 12 hours to obtain a sodium alginate solution with a mass fraction of 5 to 10%.
7. The preparation method according to claim 1, characterized in that: The step of preparing chitosan solution is to dissolve chitosan with a deacetylation degree of 87.5±7.5% and a weight average molecular weight of 180 kilodaltons in a mixture of acetic acid and deionized water with a pH value of 5 and stir for 8 to 12 hours to obtain a chitosan solution with a mass fraction of 5 to 10%.
8. The preparation method according to claim 1, characterized in that: The step of preparing the mixed solution specifically comprises mixing the sodium alginate solution and the chitosan solution, adding glycerol accounting for 10% of the total mass of the mixed solution, adding calcium peroxide with a mass fraction of 1 to 3%, and stirring for 20 to 60 minutes to obtain the mixed solution.
9. The preparation method according to claim 1, characterized in that: The steps for preparing aerogel are as follows: introducing the mixed solution into a 24-well plate, freezing it at a temperature of minus 20±5 degrees Celsius for 24 to 48 hours, and drying the frozen mixed solution in a freeze dryer at a temperature of minus 40±10 degrees Celsius for 36 to 48 hours.
10. The preparation method according to claim 1, characterized in that: The step of hot pressing and compounding is specifically to hot press for 10 to 15 minutes at a temperature of 40 to 60 degrees Celsius and a pressure of 10 to 15 MPa to obtain the double-layer diabetic wound composite dressing.